PENGEMBANGAN STRATEGIS INDUSTRI PENGEMBANG GAME LOKAL INDONESIA: PENDEKATAN BERBASIS SWOT UNTUK MEMBUKA POTENSI EKONOMI KREATIF - Nurohman, Yulfan Arif; Isa, Muzakar (STIE AMA Salatiga, 2025)
Abstract : The local game development industry in Indonesia holds significant potential to contribute to the national creative economy. However, despite substantial increases in labor absorption and market size, the sector’s contribution to national GDP and export value remains relatively low compared to other creative sub-sectors, such as fashion. Furthermore, the discrepancy between labor force growth and declining GDP performance raises concerns about productivity and industrial efficiency. This study aims to analyze the internal strengths and weaknesses, as well as external opportunities and threats (SWOT), that influence the strategic positioning of local game developers. Drawing on qualitative data gathered from key industry informants and validated through a SWOT matrix analysis (IFAS and EFAS), this research formulates strategic recommendations to enhance competitiveness and promote sustainable growth in both domestic and international markets. The findings offer practical insights for stakeholders—including policymakers, industry players, and investors—on how to develop adaptive and proactive strategies to advance Indonesia’s game development sector as a key driver of the creative economy.Abstrak : Industri pengembangan game lokal di Indonesia memiliki potensi yang signifikan untuk berkontribusi pada ekonomi kreatif nasional. Namun peningkatan substansial dalam penyerapan tenaga kerja dan ukuran pasar, kontribusi sektor ini terhadap PDB nasional dan nilai ekspor masih relatif rendah dibandingkan dengan subsektor kreatif lainnya seperti fashion. Selain itu, perbedaan antara pertumbuhan tenaga kerja dan penurunan kinerja PDB menimbulkan kekhawatiran mengenai produktivitas dan efisiensi industri. Penelitian ini bertujuan untuk menganalisis kekuatan dan kelemahan internal, serta peluang dan ancaman eksternal (SWOT), yang memengaruhi posisi strategis pengembang game lokal. Dengan menggunakan data kualitatif yang diperoleh dari informan industri utama dan divalidasi melalui analisis matriks SWOT (IFAS dan EFAS), penelitian ini merumuskan rekomendasi strategis untuk meningkatkan daya saing dan pertumbuhan berkelanjutan di pasar domestik dan internasional. Temuan ini memberikan wawasan praktis bagi para pemangku kepentingan pembuat kebijakan, pelaku industri, dan investor dalam merumuskan strategi adaptif dan proaktif untuk mendorong pengembangan sektor pengembangan game Indonesia sebagai penggerak ekonomi kreatif.